Macrostylopyga gen. nov., a new genus of cockroaches (Dictyoptera: Blattidae), with descriptions of two new species - Anisyutkin, Leonid N.; Anichkin, Alexandr E.; Thinh, Nguyen Van (Zootaxa, 2013)
The genus Macrostylopyga gen. nov. and two species (M. grandis sp. nov. and M. bidupi sp. nov.) are described. A de-tailed morphological description with special attention to the male genitalic structures is provided. Some aspects of the evolution of wingless cockroaches are briefly discussed.